The Impact of Air Pollution on Health, Economy, Environment and Agricultural Sources 2011
DOI: 10.5772/17660
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Air Pollutants on Vegetation and the Role of Vegetation in Reducing Atmospheric Pollution

Abstract: The main air pollutants are represented by gases forms, particles in suspension, different ionizing radiation and noise. The gases forms are: oxidized and reduced forms of carbon (CO 2 , CO, CH 4 ), of nitrogen (NO 2 , NO, N 2 O 4 , NH 3 , NH 4+ ), SO 2 , O 3 , C 6 H 6 vapours, Hg, volatile phenols, Cl 2 , etc. The particulate forms are: PM10 and PM2.5 particulate matter, heavy metals with toxic effect (Pb, Ni, Cd, As), polycyclic aromatic hydrocarbons PAHs, etc. Atmospheric pollutants have a negative effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 13 publications
0
41
0
Order By: Relevance
“…Modest concentrations can be a sulphur source. After entering through stomata following the same pathway as CO 2 , it may be utilised in a 'reductive sulphur cycle' to form amino acids needed for growth and development [60].…”
Section: Somentioning
confidence: 99%
“…Modest concentrations can be a sulphur source. After entering through stomata following the same pathway as CO 2 , it may be utilised in a 'reductive sulphur cycle' to form amino acids needed for growth and development [60].…”
Section: Somentioning
confidence: 99%
“…The study [2] found that smoke from the agriculture waste contributed to the urban air pollution as well as from the open fires generated at sunset (when it is less likely to get observed), which is the worst time for Cairo's air quality. Besides, it is reported that Cairo's increased ozone during summer is transported from Europe [82], and the CO increases as a result of the Khamsin events and industrial pollution [14]. A study also showed that the anticyclone flow of the Asian summer monsoon can transport the pollution from Asia toward Africa [83].…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, the World Bank characterized the air quality in Cairo as the "worst" in the world with regard to particulate matter concentration [13]. Much higher and frequent air pollution episodes were recorded recently in Cairo, threatening the public health of its over 20 million population [3], since human lungs can be severely damaged by the dust, the tiny soot fragments, and pollutant particulates [14]. Besides the emission of air pollutants, naturally, Cairo is at the apex of the Nile Delta that is bounded by the Mokattam Hills and the western heights.…”
Section: Introductionmentioning
confidence: 99%
“…A steady rise in car use, a lack of ring roads, and the presence of a built-up area result in unacceptably high levels of gas and fumes, including . NO 2 may lead to a range of pathological conditions in plant cells, for example damage to the chloroplast membranes and necrosis, which may limit the release of pollen in the tested plants [30].…”
Section: Possible Reasons For the Observed Trendsmentioning
confidence: 99%